(untitled) (Research, Society and Development, 2022)
The aim of this study is analyzed as related to kidney problems, with an emphasis on kidney function and nursing care for patients on hemodialysis at the edge. With regard to, a bibliographic and documentary analysis was used through national and international scientific articles, dissertations and theses indexed in databases such as Biblioteca Virtual de Saúde and PUBMED, in the last 10 years. This study was carried out in three aspects for the understanding of the investigated proposal: the Kidneys and a Renal Insufficiency; hemodialysis as a treatment modality for renal dysfunction and nursing care with hemodialysis at the bedside. Through professional results for the development of specific care for these patients. Studiesm that the experience as a facilitating element for hemodialysis is care for patients at the bedside. Therefore, the presence of the nursing team is crucial in the implementation and execution of care in order to avoid and observe possible complications at the time of hemodialysis.